(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores strategies for enhancing the communication culture among future English language teachers, emphasizing the pivotal role of effective communication in language education. It examines current challenges in teacher communication skills and proposes a framework that incorporates collaborative learning, reflective practice, and technology integration. By fostering a supportive environment that encourages open dialogue and intercultural understanding, the study aims to equip future educators with the necessary tools to engage diverse student populations. The findings highlight the importance of communication as a key component in developing pedagogical competence and improving overall student outcomes in language acquisition. This research contributes to the ongoing discourse on teacher education, providing actionable insights for curriculum developers and teacher trainers.